FORMULATION AND TEST OF ANTIOXIDANT ACTIVITY LOTION ETHYL ACETATE FRACTION OF CORN SILK (Zea mays L.) - Nadyavenza Yratxe Fabiola Karamoy; Paulina M.Si; Surya Sumantri Abdullah (PHARMACON, 2022)
Corn Silk (Zea mays L.) is a plant that contains various active compounds such as flavonoids and fenols that function as antioxidants. This study aimed to test the effectivity of the antioxidant lotion ethyl acetate fraction of corn silk used the DPPH method and evaluated the physical preparations with physical properties test parameters. Corn silk was extracted using maceration method with 96% ethanol as solvent and fractionated with ethyl acetate as solvent.Lotion preparation were made into 5 formulas (F1-F5) with variations in the concentration of corn silk ethyl acetate fraction (2%-10%). The results showed that the lotion of the ethyl acetate fraction of corn silk had IC50 values respectively 128,96 ppm; 116,87 ppm; 102,96 ppm; 90,98 ppm; 64,68 ppm. F5 continued to evaluate the physical properties of the preparation. The results of the physical evaluation of the preparation showed that the lotion preparation filled the organoleptic requirements, homogeneity, pH, adhesion, spreadability. Based on the results of the study, it can be concluded that the lotion of the ethyl acetate fraction of corn silk has the effectivity as an antioxidant and fulfills the requirements for the parameters of the physical properties of the preparation.